2022
DOI: 10.3233/wor-205005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, pattern and predictors of work-related musculoskeletal disorders among oil workers in Nigeria

Abstract: BACKGROUND: Work-related musculoskeletal disorders (WMSD) account for a loss of GDP in most countries. The oil sector is the largest and most economically relevant industry in Nigeria, yet the impact of WMSD on workers in this industry is unknown. OBJECTIVE: To assess the prevalence, pattern and predictors of WMSD among oil workers in Nigeria. METHODS: This exploratory study was conducted in oil producing companies in Nigeria. Nordic Musculoskeletal Questionnaire was used to assess WMSD, while risk factors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Workers in the mining, oil and gas extraction industries appear to have worse chronic health conditions than the general working population until retirement ( Robinson et al, 2021 ), and we have found similar phenomena in our study, which deserve further attention. In Nigeria, where oil is the mainstay of the industry, almost all oil workers suffer from work-related musculoskeletal disorders ( Omojunikanbi et al, 2022 ). It is recommended that health management training and occupational assessment programs be provided for workers in specialized industries.…”
Section: Discussionmentioning
confidence: 99%
“…Workers in the mining, oil and gas extraction industries appear to have worse chronic health conditions than the general working population until retirement ( Robinson et al, 2021 ), and we have found similar phenomena in our study, which deserve further attention. In Nigeria, where oil is the mainstay of the industry, almost all oil workers suffer from work-related musculoskeletal disorders ( Omojunikanbi et al, 2022 ). It is recommended that health management training and occupational assessment programs be provided for workers in specialized industries.…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal disorders can cause increased absenteeism, costs, and injuries. Data suggests that approximately nine in every ten oil workers in Nigeria have Musculoskeletal disorders [37]. When working for lengthy periods, workers inhale and are exposed to more organic solvents, which exacerbate the adverse symptoms.…”
Section: Work-related Health Problemsmentioning
confidence: 99%
“…And according to the 2020/21 Labour Force Survey (LFS) of the United Kingdom, 470,000 workers are suffering from WMSDs -new or long-standing [3]; the occurrence and pattern of WMSDs in the United Kingdom are as shown in Figure 1. In Nigeria, WMSDs are especially prevalent in certain occupational sectors and industries such as transportation, warehousing, manufacturing/petroleum industry, health care, Communication services, Butchers, agriculture, and construction services [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Other risk factors include, lack of influence or control over one's job, increase pressure (e.g., to produce more), lack of or poor communication, monotonous tasks, and perception of low support (e.g., management or co-workers). Furthermore, MSDs have been reported to be associated with reduced work ability, and decreased productivity among workers, across working populations [4,[7][8][9][12][13][14]. According to the Bureau of Labour Statistics of the Department of Labour, MSDs is the diseases and/or disorders of the musculoskeletal system, and connective tissue, when the event or exposure leading to the case is bodily reaction (e.g., bending, climbing, crawling, reaching, twisting), overexertion, or repetitive motion [15].…”
Section: Introductionmentioning
confidence: 99%